Psychometric Properties of the Polish Version of the Social Interaction Anxiety Scale and the Social Phobia Scale: Validity, Reliability and Factor Structure: Factor structure, reliability, and validity - Ciżkowicz, Barbara (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
Social anxiety is the experience of stress and discomfort associated with social situations and the fear of negative evaluation by others. The aim of this study was to assess the psychometric properties of the Polish version of two related scales: Social Interaction Anxiety Scale (SIAS) and Social Phobia Scale (SPS). The study was conducted on a non-clinical sample of 698 people (M=26.1; SD=8.18; 55% female). Factor structure, internal consistency and content validity, criterion convergent and discriminant validity were assessed for the SIAS and SPS, analysed separately and together. Reliability of the scales was high. Values of all Cronbach’s α and McDonald’s ωt coefficients were > 0.90. The factor structure of the scales was confirmed. The fit indices had acceptable values for the single factor SIAS model, three factor SPS model and for the bifactor model for the combined SIAS + SPA scales. It was found that the Polish versions of the SIAS and SPS scales are tools with good psychometric properties and can be used together to assess social anxiety in general or employed separately as reliable measures of two aspects of social anxiety: fear of interaction (SIAS) and fear of negative evaluation (SPS).